Ena/VASP: towards resolving a pointed controversy at the barbed end - Bear, James E. (Company of Biologists, 2009)
Ena/VASP proteins are conserved regulators of actin dynamics that have important roles in several physiological processes such as morphogenesis, axon guidance, endothelial barrier function, and cancer cell invasion and metastasis. Although considerable evidence points towards an anti-capping mechanism for Ena/VASP function, some controversy remains. Here, we evaluate the evidence for and against the anti-capping hypothesis, including results from some recent structural and biochemical studies that shed new light on this issue. In addition, we describe several alternate mechanisms that Ena/VASP proteins may utilize to regulate actin dynamics in vivo, including inhibition of branching, bundling and profilin-actin recruitment.